Identifying cost-effective invasive species control to enhance endangered species populations in the Grand Canyon, USA. (April 2018) - Bair, Lucas S.; Yackulic, Charles B.; Springborn, Michael R.; Reimer, Matthew N.; Bond, Craig A.; Coggins, Lewis G.
Abstract: Recovering endangered species populations when confronted with the threat of invasive species is an ongoing natural resource management challenge. While eradication of the invasive species is often the optimal economic solution, it may not be a feasible nor desirable management action in other cases. For example, when invasive species are desired in one area, but disperse into areas managed for endangered species, managers may be interested in persistent, but cost-effective means of managing dispersers rather than eradicating the source. In the Colorado River, a nonnative rainbow trout ( Oncorhynchus mykiss ) sport fishery is desired within Glen Canyon National Recreation Area, however, dispersal downriver into the Grand Canyon National Park is not desired as rainbow trout negatively affect endangered humpback chub ( Gila cypha ). Here, we developed a bioeconomic model incorporating population abundance goals and cost-effectiveness analyses to approximate the optimal control strategies for invasive rainbow trout conditional on achieving endangered humpback chub adult population abundance goals. Model results indicated that the most cost-effective approach to achieve target adult humpback chub abundance was a high level of rainbow trout control over moderately high rainbow trout population abundance. Adult humpback chub abundance goals were achieved at relatively low rainbow trout abundance and control measures were not cost-effective at relatively high rainbow trout abundance. Our model considered population level dynamics, species interaction and economic costs in a multi-objective decision framework to provide a preferred solution to long-run management of invasive and native species.